2022
DOI: 10.3389/fonc.2022.933922
|View full text |Cite
|
Sign up to set email alerts
|

EV-Mediated Chemoresistance in the Tumor Microenvironment: Is NF-κB a Player?

Abstract: Drug resistance is a major impediment to patient survival and remains the primary cause of unsuccessful cancer therapy. Drug resistance occurs in many tumors and is frequently induced by chemotherapy which triggers a defensive response both in cancerous and cancer-associated cells that constitute the tumor microenvironment (TME). Cell to cell communication within the TME is often mediated by extracellular vesicles (EVs) which carry specific tumor-promoting factors able to activate survival pathways and immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 178 publications
0
2
0
Order By: Relevance
“…It is known that the intercellular communication between TAMs, TME and several cancer cells, including breast cancer cells, is also mediated by EVs [122]. A recent study uncovered that TAM-derived EVs enriched with miR-660 inhibit Kelch-like protein 21 (KLHL21) in breast cancer cells leading to the activation of NF-κB p65 signaling pathway.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the intercellular communication between TAMs, TME and several cancer cells, including breast cancer cells, is also mediated by EVs [122]. A recent study uncovered that TAM-derived EVs enriched with miR-660 inhibit Kelch-like protein 21 (KLHL21) in breast cancer cells leading to the activation of NF-κB p65 signaling pathway.…”
Section: Breast Cancermentioning
confidence: 99%
“…Several pieces of evidence showed that TAMs sustain the initiation and progression of CRC by regulating several processes including tumor proliferation, metabolism, immunosuppression, angiogenesis and metastasis [124]. In CRC, intratumoral macrophages exert tumor-promoting functions, while TAMs found in the tumor invasive front correlate with better prognosis [122,123]. However, mixed macrophage populations are observed in human colorectal cancer tumors [125].…”
Section: Colon Cancermentioning
confidence: 99%
“…It is known that the intercellular communication between TAMs, TME and several cancer cells, including breast cancer cells, is also mediated by EVs [115]. A recent study uncovered that TAMderived EVs enriched with miR-660 inhibit Kelch-like Protein 21 (KLHL21) in breast cancer cells leading to the activation of NF-κB p65 signaling pathway.…”
Section: Breast Cancermentioning
confidence: 99%
“…Several evidence showed that TAMs sustain the initiation and progression of CRC by regulating several processes including tumour proliferation, metabolism, immunosuppression, angiogenesis and metastasis [117]. In CRC intratumoral macrophages exert tumor-promoting functions while TAMs found in the tumour invasive front correlate with better prognosis [115,116]. However, mixed macrophage populations are observed in human colorectal cancer tumours [118].…”
Section: Colon Cancermentioning
confidence: 99%